Delayed norovirus epidemic in the 2009–2010 season in Japan: potential relationship with intensive hand sanitizer use for pandemic influenza. Issue 12 (15th June 2016) - INAIDA, S.; SHOBUGAWA, Y.; MATSUNO, S.; SAITO, R.; SUZUKI, H.
SUMMARY: Norovirus (NoV) epidemics normally peak in December in Japan; however, the peak in the 2009–2010 season was delayed until the fourth week of January 2010. We suspected intensive hand hygiene that was conducted for a previous pandemic influenza in 2009 as the cause of this delay. We analysed the NoV epidemic trend, based on national surveillance data, and its associations with monthly output data for hand hygiene products, including alcohol-based skin antiseptics and hand soap. The delayed peak in the NoV incidence in the 2009–2010 season had the lowest number of recorded cases of the five seasons studied (2006–2007 to 2010–2011). GII.4 was the most commonly occurring genotype. The monthly relative risk of NoV and monthly output of both alcohol-based skin antiseptics and hand soap were significantly and negatively correlated. Our findings suggest an association between hand hygiene using these products and prevention of NoV transmission.